2016
DOI: 10.1182/asheducation-2016.1.170
|View full text |Cite
|
Sign up to set email alerts
|

The value of quality of life assessment in chronic myeloid leukemia patients receiving tyrosine kinase inhibitors

Abstract: The development of the oral tyrosine kinase inhibitors (TKIs) to treat chronic myeloid leukemia (CML) is one of the great triumphs of cancer research. Although the efficacy of TKIs has dramatically improved the disease-specific overall survival rate, the prevalence of CML is increasing worldwide. Currently, CML patients receive prolonged (even lifelong) treatment, and over the last decade, clinical decision making has become challenging. Therefore, consideration of the effects of TKI therapies on patients' qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Recent data have revealed that an increasing number of patients may gradually achieve a deep molecular response (DMR) if they continue to use second‐generation TKI for several years . However, increasing concern surrounds the long‐term adverse effects and financial burden associated with TKI …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data have revealed that an increasing number of patients may gradually achieve a deep molecular response (DMR) if they continue to use second‐generation TKI for several years . However, increasing concern surrounds the long‐term adverse effects and financial burden associated with TKI …”
Section: Introductionmentioning
confidence: 99%
“…6, 7 However, increasing concern surrounds the long-term adverse effects and financial burden associated with TKI. [8][9][10][11][12] To address these concerns, the possibility of imatinib cessation has been extensively studied. In a prospective study first presented by a French group (STIM study), approximately 39% of CML patients who maintained DMR for ≥2 years while using first-line imatinib could safely stop taking the drug after >6 months, 13 although patients who had received therapy for >5 years or had a low Sokal score were significantly more successful.…”
mentioning
confidence: 99%
“…Additional assessments that specifically address disease and treatment‐related symptoms, such as the MD Anderson Symptom Inventory for CML, in conjunction with HRQOL instruments could also be used in future studies of bosutinib to provide greater insight into the cumulative impact of bosutinib‐related AEs on HRQOL. For additional information on quality‐of‐life assessment in patients with CML receiving TKIs, the reader is referred to a comprehensive review by Efficace and Cannella …”
Section: Discussionmentioning
confidence: 99%
“…For additional information on quality-of-life assessment in patients with CML receiving TKIs, the reader is referred to a comprehensive review by Efficace and Cannella. 26 Because CML patients are living longer with TKIs, they may be on treatment for long periods of time. Therefore, it is important to assess the long-term impact of treatment on patient HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the improvement in survival seen in CML after the use of targeted drugs, now approaching that of general population 18 , has brought up the need for investigators to explore QoL, because it directly affects patient compliance to lifelong treatment. In this context, even low-grade adverse effects can substantially impair daily life of CML patients and, therefore, negatively affect adherence to therapy and clinical response 19,20 . From this perspective, the role of the patient is becoming increasingly relevant, and the patient's reported outcome assessment (PRO) is rapidly changing clinical and research practice in the setting of hematologic neoplasms.…”
mentioning
confidence: 99%